Cognitive decline and brainstem hypometabolism in long COVID: A case series. Issue 4 (15th March 2022) - Hugon, Jacques; Queneau, Mathieu; Sanchez Ortiz, Marta; Msika, Eva Flore; Farid, Karim; Paquet, Claire
Abstract: Objective: To assess FDG cerebral PET in patients suffering from cognitive impairment linked to Long COVID. The COVID pandemic has affected dozens of millions of people around the world and has resulted in the deaths of more than 3 million people. Following the acute forms, it has been reported sometimes long forms of COVID, with involvements of several organs including the brain. Neurological complications can include cognitive disturbances (brain fog) that are very common and can seriously disturb the life of patients. Methods: Fluorodeoxyglucose PETs were performed in 3 patients with cognitive decline following COVID infection. Results: We report here 3 cases of brain fog with major hypometabolic areas of the pons revealed by the cerebral FDG PET. Conclusion: The dysfunction of the locus coeruleus in these patients could partly explain the cognitive disorders observed. Further studies involving larger cohorts of patients suffering from cognitive dysfunction will be needed to determine if the brainstem is frequently affected in these patients. Abstract : Cognitive deficits linked to long COVID can be associated with brainstem hypometabolic areas on the FDG PET scan.